Western Balkans Labor Market Trends 2018 - World Bank Group (World Bank, Washington, DC, 2018)
This report is the second in a series, presenting labor market developments in the Western Balkan countries in 2017 and comparing with selected member states of the European Union (EU). The report is the result of collaboration between the World Bank and the Vienna Institute for International Economic Studies (WIIW) and is based on the South-Eastern Europe (SEE) jobs gateway database on labor market indicators. That database uses labor force survey (LFS) data provided by the statistical offices of the individual Western Balkan countries, and by Eurostat for the EU comparator countries, and is available online at the SEE jobs gateway. The objective of this report is to showcase these data for a general, non-technical audience, and present a few insights into how labor markets in the Western Balkans have developed over the past year. This year’s report includes a special topic on improving data and knowledge about labor mobility from the Western Balkans.